PENGEMBANGAN MEDIA POP UP BOOK MATERI MINYAK BUMI BERBASIS SOSIO-SCIENTIFIC ISSUE (SSI) - Ilvio Miranti; Fitri Refelita (Journal of Chemistry Education and Integration, 2023)
This research were investigated by the lack of socio-scientific issue (SSI)-based pop up book media. This research aimed at designing SSI-based pop up book media on crude oil lesson. Research and development (R&D) method was used in this research with borg and gall model that was limited to the fifth stage. The stages were collecting the data, planning, developing the product, testing the product, and revising. SSI-based pop up book media on crude oil lesson was tested valid with the percentage 94.4% (very valid), it was tested practical with the percentage 96.1% (very practical), and it got good response to overall content of pop up book with the percentage 96.7% (very practical). Based on these findings, it could be concluded that SSI-based pop up book media on crude oil lesson was proper to be used as a learning media for students at school.Keywords : Pop Up Book, Socio-Scientific Issue (SSI), Crude Oil